2008
DOI: 10.1063/1.2830832
|View full text |Cite
|
Sign up to set email alerts
|

High pressure phase transitions and compressibilities of Er2Zr2O7 and Ho2Zr2O7

Abstract: Phase stability and compressibility of rare earth zirconates with the defect-fluorite structure were investigated by in situ synchrotron x-ray diffraction. A sluggish defect-fluorite to a cotunnitelike phase transformation occurred at pressures of ∼22 and ∼30GPa for Er2Zr2O7 and Ho2Zr2O7, respectively. Enhanced compressibility was found for the high pressure phase as a result of increasing cation coordination number and cation-anion bond length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(84 citation statements)
references
References 19 publications
8
76
0
Order By: Relevance
“…The high-pressure phase has nanometer scale grain size, which was observed before in quenched pyrochlores [33] by TEM analysis. Previous research revealed that pressure-induced phase transition in RE 2 Zr 2 O 7 pyrochlore or distorted-fluorite structure is reversible [30]. Quick unloading of pressurized sample with He pressure medium may easily break the diamond anvils because of the strain generated by the penetration of He across the diamond surface layer at high pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The high-pressure phase has nanometer scale grain size, which was observed before in quenched pyrochlores [33] by TEM analysis. Previous research revealed that pressure-induced phase transition in RE 2 Zr 2 O 7 pyrochlore or distorted-fluorite structure is reversible [30]. Quick unloading of pressurized sample with He pressure medium may easily break the diamond anvils because of the strain generated by the penetration of He across the diamond surface layer at high pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…45 The dioxides UO 2 , ThO 2 , ZrO 2 and HfO 2 undergo a transition into the cotunnite structure at high pressure, and Li 2 O transforms to an anti-cottunite structure. [46][47][48] Analysis of our results for zirconolite-III using a Pnma cell with a = 5.357(5) Å, b = 3.128(1) Å and c = 6.372(9) Å provides an excellent fit to the diffraction data, and a full Reitveld refinement using this structure model also led to a good fit (Figure 12 (d)).…”
Section: Formation Of a Disordered Phase At Higher Pressure And Its Rmentioning
confidence: 99%
“…3,7,8 The high radiation and chemical stability and low neutron absorption coefficients of Zr make zirconate pyrochlores extremely useful for these purposes, but recent studies have found pressure-driven instabilities. 9 Structural transitions were reported for Sm 2 [10][11][12] Studies on related Y 2 Zr 2 O 7 indicated the formation of a defect-cotunnite structure at 18 GPa. 13 HP x-ray diffraction (XRD) and Raman studies of La 2 Hf 2 O 7 revealed no phase transition and instead showed decomposition to the constituent oxides.…”
mentioning
confidence: 99%